2018
DOI: 10.3389/fmed.2017.00247
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Tissue Oxygenation: an Everyday Clinical Challenge

Abstract: Purpose of reviewThe aim of this article is to study the overview of pathophysiology and clinical application of central venous oxygen saturation monitoring in critically ill patients and during the perioperative period.Recent findingsThere are several clinical studies and animal experiments evaluating the effects of goal-directed hemodynamic stabilization on critically ill patients. Recent systematic reviews and meta-analyses found that advanced hemodynamic endpoints-targeted management has a positive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The oxygen extraction rate (OER in Fig.4c), an indication of the oxygen uptake by cells, was calculated as OER=(O ca -O cv )/O ca , whereby O ca and O cv is the oxygen saturation in the central artery and vein, respectively 27 . We observed that OER slightly dropped shortly after the Air supply period, suggesting a delayed response in cell oxygenation.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen extraction rate (OER in Fig.4c), an indication of the oxygen uptake by cells, was calculated as OER=(O ca -O cv )/O ca , whereby O ca and O cv is the oxygen saturation in the central artery and vein, respectively 27 . We observed that OER slightly dropped shortly after the Air supply period, suggesting a delayed response in cell oxygenation.…”
Section: Resultsmentioning
confidence: 99%
“…Information on the molecular composition of tissue types is sparse and scattered throughout the literature. SIMPA models the properties of different skin layers and muscle tissue using the review article of Bashkatov et al., 55 melanin content in the epidermis using Alaluf et al., 56 the water volume fractions of different tissue types in the human body using Timmins and Wall 57 and Forbes et al., 58 and the distribution of arterial and venous blood oxygenations using Molnar and Nemeth 59 and Merrick and Hayes. 60…”
Section: Simpa Toolkitmentioning
confidence: 99%
“…La extracción de oxígeno (O 2 ER) es la relación entre el VO 2 y el aporte de oxígeno (DO 2 ) 11 . La O 2 ER representa el porcentaje de oxígeno que la célula extrae de la sangre arterial.…”
Section: Evaluación De La Extracción De Oxígenounclassified